Les batiments et les equipements d' archives / Archives buildings and equipment / conceived by the Committe on Archival Buildings and Equipment of the International Council on Archives. -- - Duchein, Michel (Collection de supports de cours. Teaching aids series ;, 1993)
Sumario: Se resalta la importancia de la conservacion fisica y laexplotacion de los documentos que se encuentran en los archivos ; asi como el local que se debe emplear y las condiciones que debe renir.